A Case Report: A 11-Years Old Female with Retinitis Pigmentosa - Vania, Vania; Faozan, Faozan; Felix, Felix (Syntax Literate, 2024)
Retinitis pigmentosa is a hereditary retinal neurodegenerative disease with the classic presentation of night blindness (nyctalopia), with gradual degeneration of vision until blindness). This study aims to analyze a clinical case of retinitis pigmentosa (RP) in an 11-year-old female with primary symptoms of nyctalopia, progressing visual impairment, and distinctive retinal pigmentation changes identified during funduscopy. RP is a hereditary retinal degenerative condition that commonly presents as night blindness, progressing to severe vision loss or blindness. In this case, a comprehensive physical and ophthalmic examination revealed decreased visual acuity, refractive errors, and vascular attenuation, characteristic of RP, without systemic abnormalities or familial history, classifying it as a sporadic case. Given that RP is typically inherited in autosomal dominant, autosomal recessive, or X-linked patterns, sporadic cases are rarer and require careful diagnosis. This study underscores the importance of thorough ocular assessments, particularly fundus examinations, in identifying early retinal changes in RP, as well as the challenges in diagnosis without a family history. The findings emphasize that, while RP is primarily ocular, extraocular manifestations in syndromic forms also exist. RP remains a major cause of blindness worldwide, and while emerging treatments—such as gene therapy and retinal implants—offer new potential, a standardized management protocol is yet to be established. This study advocates for continued research into targeted therapeutic options to improve outcomes and quality of life for RP patients, and highlights the need for early diagnosis and ongoing monitoring to manage disease progression effectively.